Application of salinomycin in treatment of different types of cancer - Noreen, Saba; Umar, Hussan Bin; Asghar, Rameesha; Naz, Fariha; Naz, Farah (Journal of Agriculture and Biology, 2025)
Cancer occurs when the delicate balance between proliferation of cell and regulation is disturbed. Genes that inhibit tumors stop working when proto-oncogenes turn into oncogenes, which results to uncontrolled cell growth. KRAS, MYC, and HER2 are oncogenes. Cancer cells control potassium K⁺ levels in order to fight against treatments. This equilibrium is upset by salinomycin, it brings K⁺ ions and forces them out of the cell. Particularly in cancer stem cells (CSCs), this effects survival signals, manufacturing of proteins, and mitochondrial function, result in apoptosis. CSCs depend on ABC transporters for resistance to drugs, which salinomycin inhibits, rendering them susceptible to treatment. It blocks Wnt/β-catenin and Hedgehog signaling pathways, preventing cancer cell proliferation. Salinomycin also causes ER stress and cell death by upsetting Ca²⁺ homeostasis. The SlnR pathway, which governs antibiotic production in Streptomyces albus, regulates its biosynthesis. Salinomycin’s ability to inhibit multiple cancer mechanisms renders it an appealing anticancer agent. While challenges in manufacture, purification, and toxicity must be addressed, the present data shows the possibility of salinomycin as a beneficial supplement to cancer therapy. Despite exhibiting positive effects in severe cancer cases, its use in medicine is still restricted due to concerns about possible damage to healthy cells. The goal of study is to implement salinomycin in clinical practice.
Keywords: Streptomyces albus; salinomycin; cancer stem cells (CSCs); antibiotic; antimicrobial peptide; cancer treatment